Clinical management of constipation – the role of physical activity - systematic review - Flanczewski, Sebastian; Gajek-Flanczewska, Wiktoria; Walczak, Agata; Wirkijowski, Jakub; Niegowska, Wiktoria; Woźniak, Paulina; Kidacki, Kajetan; Wiklińska, Agata; Śliwińska, Martyna; Wójtowicz, Katarzyna; et al. (Quality in Sport, 2024)
Constipation is a prevalent gastrointestinal disorder that affects a significant portion of the global population, yet its management remains challenging due to its complex etiology. This review explores the potential benefits and mechanisms of physical activity in alleviating constipation symptoms. We examined recent studies on the physiological effects of various exercise types and intensities on bowel movements, gastrointestinal blood flow, and microbiome composition. Our findings suggest that aerobic exercise enhances colonic motility and accelerates gastrointestinal transit, though the effects vary depending on exercise duration and intensity. While light to moderate physical activity (less than 60 minutes) appears beneficial, prolonged or intense exercise may inhibit motility and exacerbate symptoms. Additionally, exercise-induced changes in the gut microbiome and blood flow dynamics were observed, influencing stool consistency and colonic function. However, the interplay between diet, hydration, and physical activity is crucial, as adequate dietary fiber and hydration are essential for optimizing exercise’s impact on constipation. Although evidence supports the role of physical activity in managing constipation, further research is needed to clarify the most effective exercise regimens and their integration with dietary and lifestyle modifications.